2017
DOI: 10.1371/journal.pone.0181619
|View full text |Cite
|
Sign up to set email alerts
|

The association between car accident fatalities and children’s fears: A study in seven EU countries

Abstract: Children’s fear of a car accident occurring to parents or themselves has been used as a concrete example to illustrate one of the symptoms of anxiety disorders such as separation anxiety and generalized anxiety. However, its usage across countries may be questionable where the prevalence of this specific type of injury differs. This cross-sectional study compares samples from seven diverse European countries (Bulgaria, Germany, Italy, Lithuania, Netherlands, Romania, Turkey) to see if an environmental exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
2
0
1
Order By: Relevance
“…Moreover, Germany has a lower overall death rate for COVID-19 (5.0 %) as compared to China (5.6 %) as of May 17, 2020 (https://www.worldometers. info/coronavirus/#countries), and previous studies suggest that self-reported fear is positively associated with death rate by country [3]. Indeed, the majority of respondents (39.3 %) reported being "worried in general" during the ongoing COVID-19 pandemic.…”
mentioning
confidence: 83%
“…Moreover, Germany has a lower overall death rate for COVID-19 (5.0 %) as compared to China (5.6 %) as of May 17, 2020 (https://www.worldometers. info/coronavirus/#countries), and previous studies suggest that self-reported fear is positively associated with death rate by country [3]. Indeed, the majority of respondents (39.3 %) reported being "worried in general" during the ongoing COVID-19 pandemic.…”
mentioning
confidence: 83%
“…Knowing and applying intervention strategies for the prevention of TA has been the objective of studies, which has found, in its results, that the behavior of children and adolescents tends to be influenced by the example of their caregivers or companions. This behavior also happens in relation to traffic (16)(17) . Thus, performing isolated activities has not been an efficient strategy.…”
Section: Discussionmentioning
confidence: 69%
“…Es necesario señalar que el miedo y la ansiedad son diferentes entre sí. Kovess-Masfety et al(2017) Mencionan que el miedo es una respuesta racional a un evento peligroso que se vive y con frecuencia éste se convierte en ansiedad, la cual es considerada una respuesta irracional ante una amenaza que se percibe incorrectamente como más grave y apremiante de lo que es en realidad. Onder et al (2018) Señalan que Craig, Brown y Baum en 1995 postulaban que la ansiedad es una respuesta general a una amenaza desconocida o a un conflicto interno, mientras que el miedo se centra en amenazas externas.…”
Section: Revista Iberoamericana De Psicologíaunclassified